2012
DOI: 10.1016/j.snb.2012.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Detection of volatile organic compounds in cattle naturally infected with Mycobacterium bovis

Abstract: We report here on a novel methodology in detecting Mycobacterium bovis (M. bovis) infection in cattle, based on identifying unique volatile organic compounds (VOCs) or a VOC profile in the breath of cattle. The study was conducted on an M. bovis-infected dairy located in southern Colorado, USA, and on two tuberculosis-free dairies from northern Colorado examined as negative controls. Gaschromatography/mass-spectrometry analysis revealed the presence of 2 VOCs associated with M. bovis infection and 2 other VOCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
103
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 40 publications
(65 reference statements)
1
103
0
1
Order By: Relevance
“…Interestingly, those authors reported quantitative differences (increase or decrease) in VOC detection in relation to infection (79). A recent investigation in cattle employed GC-MS to select 2 pathogen-related VOCs in the breath of Mycobacterium bovis-infected animals and 2 VOCs associated with healthy noninfected animals (80). These candidate VOC biomarkers (cyclohexane and pentadine) were utilized for designing an array of sensors based on nanotechnology for detecting M. bovis-infected cattle.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, those authors reported quantitative differences (increase or decrease) in VOC detection in relation to infection (79). A recent investigation in cattle employed GC-MS to select 2 pathogen-related VOCs in the breath of Mycobacterium bovis-infected animals and 2 VOCs associated with healthy noninfected animals (80). These candidate VOC biomarkers (cyclohexane and pentadine) were utilized for designing an array of sensors based on nanotechnology for detecting M. bovis-infected cattle.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…These candidate VOC biomarkers (cyclohexane and pentadine) were utilized for designing an array of sensors based on nanotechnology for detecting M. bovis-infected cattle. In field settings, this device identified all the infected animals and detected probable cases of infection among 21% of noninfected animals (80).…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…This method also has the potential to diagnose lung cancer at an early stage by detecting volatile organic compound (VOC) biomarkers in exhaled breath. [6][7][8][9] As such, a number of breath-analysis tools have been developed including gas chromatography/mass spectrometry, [10][11][12][13][14] ion flow tube mass spectrometry, 15,16 chemo-luminescence sensors, 17 optochemical fibers, 18 infrared spectroscopy, 19 and polymer-coated surface acoustic wave sensors. 20 Incorporating most of the conventional breath analysis techniques into portable sensing devices is difficult, however, owing to the bulky and expensive nature of these instruments and complexity of their operation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] These arrays could meet the growing demand for rapid and flexible online detection of a wide range of chemical and biological agents in different branches of industry, homeland security, 5,6 environmental monitoring, 5,7,8 and medical diagnostics [1][2][3][4][5][9][10][11][12][13][14][15][16][17][18][19][20] . Combined with statistical algorithms, these sensor arrays can provide convenient bionics of the mammalian olfactory system for identifying complex gas samples, without the necessity of identifying their separate ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors with electronic and electro-acoustic transduction mechanisms, such as chemically sensitive resistors [24][25][26][27][28][29][30][31][32][33] and quartz-crystal microbalance (QCM) sensors [34][35][36] are among the most attractive and widespread elements for sensing applications that involve the detection and classification of volatile organic compounds (VOCs) in the gas phase. 9,11,13,16,19,20,24,37 Recently, we have shown that polycyclic aromatic hydrocarbon (PAH) derivatives as sensing materials in chemiresistors, field effect transistors or QCM sensors can provide good sensitivity and robust selectivity towards different polar and nonpolar VOCs, while being highly tolerant even to drastic humidity variations. 11,33,34,[38][39][40] For example, we have shown that a bilayer structure with a quasi 2D network of single wall carbon nanotubes (RNSWCNTs) as an under-layer and a micron-thick PAH film as an overcoat, can provide excellent detection and classification between polar and nonpolar VOCs, both in dry atmospheres with ~ 5% relative humidity (RH) and in almost fully humidified atmospheres (~80% RH).…”
Section: Introductionmentioning
confidence: 99%